2005
DOI: 10.1021/om050009f
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Intrinsic Reactivities of Various Allylmetals toward Carbonyls and Water

Abstract: Quantum mechanics MP2/6-31+G* calculations have been carried out for the reactions of a series of monomeric allylmetals with water and carbonyl compounds in the gas phase. Allyl complexes of groups IA and IIA and low-valent group IIIA and IVA metals are π-complexes or reactive σ-complexes. They show high reactivities toward hydrolysis. Group IIB, trivalent group IIIA, tetravalent group IVA, and both tri-and pentavalent group VA metals form σ-complexes with allyl. These allylmetals are less reactive toward hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Whether the same situation applies to beryllium allyl compounds is not entirely clear, but π bonding would not normally be expected 26. Wu et al., for example, determined that the minimum energy structure of [(C 3 H 5 )BeBr] at the MP2//HF level of theory contains a σ‐bound allyl ligand 27. However, John and co‐workers computationally modeled the allyl ligand in the compound [(η 3 ‐C 3 H 5 )BeAs( t ‐Bu) 2 ], and found that a π‐bonded allyl group on beryllium was reasonable 23…”
Section: Methodsmentioning
confidence: 99%
“…Whether the same situation applies to beryllium allyl compounds is not entirely clear, but π bonding would not normally be expected 26. Wu et al., for example, determined that the minimum energy structure of [(C 3 H 5 )BeBr] at the MP2//HF level of theory contains a σ‐bound allyl ligand 27. However, John and co‐workers computationally modeled the allyl ligand in the compound [(η 3 ‐C 3 H 5 )BeAs( t ‐Bu) 2 ], and found that a π‐bonded allyl group on beryllium was reasonable 23…”
Section: Methodsmentioning
confidence: 99%
“…roughly linear K(1)À ÀK(2)À ÀK(1) 0 sections (170.28) alternating with strongly bent K(2)À ÀK(1)À ÀK(2) 0 angles (103. 38)], but it is difficult to ascribe chemical significance to this, given the broader structural difference between the chains (helical vs. simple undulations). [33]), indicating the similarly ionic bonding in the complexes.…”
Section: Computational Detailsmentioning
confidence: 99%
“…As befits its importance in the family of organolithium reagents, the relative stabilities and geometries of bridged (Z 3 -bound) and sigma-bonded (Z 1 -bound) allyllithium, and the influence of coordinated solvent on the structures and barriers to ligand rotation have been the subject of repeated computational studies [37,38]. The symmetrical p-bound form of Li(C 3 H 5 ) is well established as lower in energy than a ''classical'' s-bonded structure [39].…”
Section: Computational Study Of Allyllithiumsmentioning
confidence: 99%
“…Recently, Chan et al carried out a theoretical study of hydrolysis and carbonyl additions reactions for a series of allylmetals in gas phase [27]. The divalent metal allyl complexes of group 14 have similar reactivity toward hydrolysis and carbonyl addition.…”
Section: Resultsmentioning
confidence: 99%